2005
DOI: 10.1007/bf02977716
|View full text |Cite
|
Sign up to set email alerts
|

Scoparone from artemisia capillaris inhibits the release of inflammatory mediators in RAW 264.7 cells upon stimulation cells by interferon-γ plus LPS

Abstract: Scoparone is a major component of the shoot of Artemisia capillaris (Compositae), which has been used for the treatment of hepatitis and biliary tract infection in oriental countries. In the present study we observed that, scorparone exhibited no cytotoxic effect in unstimulated macrophages, but reduced the release of nitric oxide (NO) and prostaglandin E2 (PGE2) upon stimulation by IFN-gamma/LPS or LPS. The inhibitory effects were found to be in conjuction with the suppression of inducible nitric oxide syntha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 24 publications
4
45
0
1
Order By: Relevance
“…The result illustrated that the immune system of broilers was over activated, which could result in the redistribution of nutrients away from growth and towards the immune reaction, and eventually led to the decline of the growth performance. Diet supplemented with AOE significantly inhibited the increased content of serum IgA and IgG, which indicated that AOE could weaken the excessive activation of immune system, and alleviate the immune stress, Currently, the effect of AOE on immune function in broilers rarely was reported, but many studies reported that the Artemisia plants could alleviate the inflammatory response induced by LPS, and the present study was corroborated by these research results (Jang et al 2005;Yoon et al 2010;Jang et al 2015).…”
Section: Growth Performancesupporting
confidence: 83%
“…The result illustrated that the immune system of broilers was over activated, which could result in the redistribution of nutrients away from growth and towards the immune reaction, and eventually led to the decline of the growth performance. Diet supplemented with AOE significantly inhibited the increased content of serum IgA and IgG, which indicated that AOE could weaken the excessive activation of immune system, and alleviate the immune stress, Currently, the effect of AOE on immune function in broilers rarely was reported, but many studies reported that the Artemisia plants could alleviate the inflammatory response induced by LPS, and the present study was corroborated by these research results (Jang et al 2005;Yoon et al 2010;Jang et al 2015).…”
Section: Growth Performancesupporting
confidence: 83%
“…Silica gel column chromatography of fraction 6 with chloroform followed by TLC generated citropten (6) (8.2 mg) (Kawaii et al, 1999), β-sitosterone (7) (1.0 mg) (Lee and Chang, 2000), and a mixture of β-sitosterol (8) and stigmasterol (9) (1120.8 mg) (Chen et al, 1997). Fraction 7 was purified by silica gel column chromatography with chloroform-ethyl acetate (20 : 1) to give scoparone (10) (5.1 mg) (Jang et al, 2005). Separation of fraction 8 by repeated column chromatography over silica gel using n-hexane-ethyl acetate gradients followed by purification with preparative TLC on silica gel yielded diosmetin (11) (3.8 mg) (Sahu et al, 1998), chrysoeriol (12) (2.5 mg) (Choi et al, 2005), aurantiamide acetate (13) (30.2 mg) (Park et al, 2006), methyl-(21R)-pheophorbidea (14) (5.4 mg) (Lai et al, 2010), mixture of β-sitosteryl glucoside (15) and stigmasteryl glucoside (16) (1081.1 mg) (Chen et al, 1999), and 2,6-dimethoxy-pbenzoquinone (1.0 mg) (17) (Nishina et al, 1991).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…For example, several coumarin derivatives exert antiinflammatory activity in vivo (Hoult and Paya, 1996). Scoparone isolated from A. capillaris was found to show anti-inflammatory activity (Jang et al, 2005) by inhibiting nitric oxide (NO) and PGE 2 production from IFN-γ and lipopolysaccharide (LPS)-treated RAW 264.7 cells. Scoparone was also found to inhibit tetradecanoylphorbol-13-acetate (TPA)-induced IL-8 and MCP-1 production in U937 cells (Jang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%